Incentives and intertemporal behavioral spillovers: A two-period experiment on charitable giving - Marius Alt; Carlo Gallier (ZEW - Leibniz-Zentrum für Europäische Wirtschaftsforschung, 2021)
We test whether and, if so, how incentives to promote pro-social behavior affect the extent to which it spills over to subsequent charitable giving. To do so, we conduct a two-period artefactual field experiment to study repeated donation decisions of more than 700 participants. We vary how participants' first pro-social behavior is incentivized by a wide range of fundraising interventions ranging from soft to hard paternalism. Our design allows us to decompose spillover effects into a pure spillover effect, which identifies the impact of previous pro-social behavior on subsequent donation decisions and a crowding effect, which captures the extent to which the spillover effects are affected by the incentives exerted on the previous pro-social behavior. We find evidence for negative spillover effects. Participants donate less if they completed a pro-social task prior to the donation decision. Most importantly, we find that the spillover effects depend on how the initial pro-social behavior has been incentivized. Especially participants who are incentivized to donate through social comparisons are more willing to give to charity thereafter compared to participants whose initial pro-social behavior is incentivized by monetary rewards. The variations in spillover effects are driven by participants' perceived external pressure in the first pro-social decision.
Keywords: C91; C93; D01; H41; D04; 330; Charitable giving; Social preferences; Experimental economics; Behavioral spillovers; Policy-making; Economic incentives